2004
DOI: 10.1152/japplphysiol.01292.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tourniquet-induced ischemia on the release of proopiomelanocortin derivatives determined in peripheral blood plasma

Abstract: fects of tourniquet-induced ischemia on the release of proopiomelanocortin derivatives determined in peripheral blood plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Prior surgical studies generally involved increasing the tourniquet pressure to above the mean arterial pressure (MAP) in order to ensure a bloodless field during extremity surgery. [6][7][8][9][10] These results may indicate that blood pressure cuff increase to above the MAP could also falsely increase lactate values in clinical practice; however, this has not been adequately studied.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Prior surgical studies generally involved increasing the tourniquet pressure to above the mean arterial pressure (MAP) in order to ensure a bloodless field during extremity surgery. [6][7][8][9][10] These results may indicate that blood pressure cuff increase to above the MAP could also falsely increase lactate values in clinical practice; however, this has not been adequately studied.…”
Section: Discussionmentioning
confidence: 98%
“…5 In orthopedic studies utilizing tourniquet for hemostasis, lactate levels have been found to increase; however, these studies also used tourniquet times far in excess of what is applied for a blood draw. [6][7][8][9][10] As a result of these studies as well as due to the theoretical reasoning for tourniquet avoidance, many hospitals have protocols in place indicating that lactate levels must be drawn without a tourniquet. Some manufacturers of lactate assays as well as the Surviving Sepsis Campaign Bundle also recommend drawing lactates without tourniquets.…”
Section: Introductionmentioning
confidence: 99%
“…A fluid-phase two-site immunoprecipitation RIA as described previously was used to determine β-END(1–31) in plasma extracts [13, 23, 24]. In brief, a monoclonal mouse antibody (code 3E7), directed against the N-terminus of β-END (YGGF), and a polyclonal rabbit antiserum (code 11P), directed against the C-terminal fragment of β-END (KKGE) were used.…”
Section: Methodsmentioning
confidence: 99%
“…13 -17 Metabolic stressors including ischemia may evoke the release of endogenous opioids from the peripheral tissues to provide protection against sustained ischemia–reperfusion injury in the heart. 40 -43 Patel et al described the putative role of opioids in mediating RIPC-induced cardioprotection in an intact rat model of myocardial infarction. Mesenteric remote preconditioning (15-minute occlusion followed by 10-minute reperfusion)-induced cardioprotective effects were completely abolished in the presence of naloxone (nonspecific opioid antagonist), suggesting that the endogenous release of opioids may mediate mesenteric remote preconditioning-induced cardioprotection.…”
Section: Role Of Opioids In Ripcmentioning
confidence: 99%